Pośmiertne życie rewolucji. O Dzienniku węgierskim Wiktora Woroszylskiego z perspektywy „nieustającej w swym ruchu historii” - Stankowska, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article is devoted to the Hungarian revolution in 1956, witnessed and described by Wiktor Woroszylski in his Hungarian diary . His report from the fighting Budapest is as important as the comments added in 1976, 1981, 1986, and 1989, the milestones of the Polish way to freedom, described by one of its participants. In the comments, Woroszylski creates a vision of “history incessant in its movement”, marked by hope and disappointment. The author points out to similarities and relationships between freedom uprisings in various Soviet-dominated countries of Central Europe.